Maxim Flouting in Turning Red Movie - Nurul Hidayah, Amanda; Bunau, Eusabinus; Suhartono, Luwandi (Universitas Teuku Umar, 2024)
Language’s role in society is pivotal. People utilize language, which includes gesture language and spoken, written, and other forms of structured communication to interact with their surroundings. It is considered flouting the conversational maxims when speakers purposefully stray from the accepted conventions of communication, frequently with a goal in mind. The research objective was to identify the four conversational maxims being flouted in the movie “Turning Red.” The research employed a descriptive research design. The data was gathered through the viewing of the movie and writing down the dialogues in which the characters flouted the four conversational maxims, as well as the types of conversational maxims being flouted, the contexts, the motivations behind the flouting of the conversational maxims, and the implicatures. The results show that four distinct types of conversational maxims are indeed being flouted in the movie “Turning Red”, such as the maxims of quantity with the percentage of 19.5% and the frequency of 7, quality with the percentage of 33.3% and the frequency of 12, relevance with the percentage of 33.3% and the frequency of 12, and manner with the percentage of 13.9% and the frequency of 5. The findings of the research indicate the potentiality of the movie as a medium to learn about pragmatics, especially the flouting of the four conversational maxims, for students.